Spinal cord and infratentorial lesions in radiologically isolated syndrome are associated with decreased retinal ganglion cell/inner plexiform layer thickness. (December 2019) - Filippatou, Angeliki; Shoemaker, Thomas; Esch, Megan; Qutab, Madiha; Gonzalez-Caldito, Natalia; Prince, Jerry L; Mowry, Ellen M; Calabresi, Peter A; Saidha, Shiv; Sotirchos, Elias S
Background: The role of retinal imaging with optical coherence tomography (OCT) in assessing individuals with radiologically isolated syndrome (RIS) remains largely unexplored. Objective: To assess retinal layer thicknesses in RIS and examine their associations with clinical features suggestive of increased risk for conversion to multiple sclerosis (MS). Methods: A total of 30 RIS subjects and 60 age- and sex-matched healthy controls (HC) underwent retinal imaging with spectral-domain OCT, followed by automated segmentation of retinal layers. Results: Overall, retinal layer thicknesses did not differ between RIS and HC. However, RIS subjects with spinal cord (SC) lesions had lower ganglion cell + inner plexiform layer (GCIP) thickness compared to HC (−4.41 μm; p = 0.007) and RIS without SC lesions (–3.53 μm; p = 0.041). Similarly, RIS subjects with infratentorial (IT) brain lesions had lower GCIP thickness compared to HC (–4.07 μm; p < 0.001) and RIS without IT lesions (–3.49 μm; p = 0.029). Multivariate analyses revealed that the presence of SC or IT lesions were independently associated with lower GCIP thickness in RIS ( p = 0.04 and p = 0.03, respectively). Other patient characteristics, including sex, abnormal cerebrospinal fluid, and presence of gadolinium-enhancing or juxtacortical lesions, were not associated with retinal layer thicknesses. Conclusion: The presence of SC or IT lesions in RIS may be associated with retinal neuro-axonal loss, supporting the presence of more disseminated disease.